PERAN ORANG TUA SINGLE PARENT DALAM MENUMBUHKAN KEMANDIRIAN IBADAH SHOLAT FARDHU PADA ANAK USIA REMAJA - Suryadi Suryadi Suryadi; Sukarno Sukarno (INSTITUT AGAMA ISLAM NEGERI METRO, 2022)
Every single parent has duties, functions, and methods that are applied to teenage children so that they can be more independent and disciplined in carrying out fardhu prayers. The purpose of this study was to determine the role of single parent parents in growing the independence of praying fardhu prayers in adolescent children. The method used in this research is using descriptive qualitative research methods. The data collection technique in this research is using observation, interview and documentation techniques. Based on the results of the study, it is known that there is good communication and cooperation between parents and children, as well as carrying out the duties and functions of parents correctly. So, the role of single parent parents in growing the independence of praying fardhu prayers in teenagers is that parents must be able to carry out their duties and functions well, and be able to establish good communication and cooperation between parents and children so that children can socialize well and Teenagers are able to carry out fardhu prayers properly without coercion from others (based on their own desires.